First results of the surface water ocean topography (SWOT) observations to rivers elevation profiles in the Cuvette Centrale of the Congo Basin - Normandin, Cassandra; Frappart, Frédéric; Baghdadi, Nicolas; Bourrel, Luc; Peña Luque, Santiago; Ygorra, Bertrand; Kitambo, Benjamin; Papa, Fabrice; Riazanoff, Serge; Wigneron, Jean-Pierre (Frontiers in Remote Sensing, 2024)
Rivers play a crucial role in maintaining ecosystems and regional climates, while also providing essential water for irrigation and drinking. With the increasing impacts of climate change and human activities, rivers are becoming more prone to extreme events (droughts and floods) and induced erosion/deposition processes, making water-related risk management more challenging. The recent launch of the Surface Water and Ocean Topography (SWOT) mission, which focuses on continental surfaces with a spatial resolution of 100 m, has opened new avenues for applications in hydrology, hydrodynamics, and geomorphology. This study examines the initial results of the SWOT mission for sixteen rivers (ranging in width from 50 to 2,000 m) in the Cuvette Centrale of the Congo Basin, obtained in April 2023 during the fast sampling phase. The study assesses water surface elevations (WSE) and backscatter coefficient (σ0) measured from SWOT. Comparisons of WSE with data from other radar altimetry missions (Sentinel-3A and 3B, Jason-3, and Sentinel-6A) and GEDI data show high correlation coefficients of 0.977 (with a bias of 0.538 m) and 0.992 (with a bias of 1.011 m), respectively. The first maps of WSE slopes show realistic values, even in rivers less than 100 m wide, with steeper slopes upstream. Various WSE longitudinal profiles are retrieved with unprecedented spatial resolution, surpassing what other nadir altimetry missions have achieved. The σ0 values, between −10 and 20 dB on average, also appear consistent with other studies. These promising initial results pave the way for future studies on fluvial geomorphology dynamics and erosion/deposition processes from the new SWOT observations.